2013
DOI: 10.1245/s10434-013-3140-1
|View full text |Cite
|
Sign up to set email alerts
|

Ki 67 is an Independent Predictive Biomarker of Cancer Specific and Local Recurrence-Free Survival After Lung Tumor Ablation

Abstract: Ki-67+ tumor cells on the electrode after pulmonary tumor RF ablation is an independent predictor of LTP, shorter LPFS, and DSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…However, there is still a significant discrepancy between complete ablation based on imaging alone and residual microscopic disease that may remain undetected at the ablation site [70]. This is supported by studies that analyzed the tissue extracted from the electrode after liver RFA [71][72][73] and correlated the identification of residual prolific [11] or viable tumor cells [74] with LTP [11,74] as well as overall patient survival, after both lung and liver tumor ablation [75]. More recently, the strong correlation between the identification of viable tumor cells and LTP was prospectively validated through biopsies performed immediately after CLM ablation with pathologic and immunohistochemical assessment of the ablation zone [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a significant discrepancy between complete ablation based on imaging alone and residual microscopic disease that may remain undetected at the ablation site [70]. This is supported by studies that analyzed the tissue extracted from the electrode after liver RFA [71][72][73] and correlated the identification of residual prolific [11] or viable tumor cells [74] with LTP [11,74] as well as overall patient survival, after both lung and liver tumor ablation [75]. More recently, the strong correlation between the identification of viable tumor cells and LTP was prospectively validated through biopsies performed immediately after CLM ablation with pathologic and immunohistochemical assessment of the ablation zone [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other markers of tumor biology may also be useful to assess. Sofocleous et al (31) have previously reported Ki-67 as a predictive biomarker after RFA. In their cohort of 47 lung tumors, 13 were known to represent primary lung cancers.…”
Section: Vascular and Interventional Radiologymentioning
confidence: 97%
“…Additional biomarkers (e.g., Ki-67, KRAS, and EGFR), inflammatory cytokines, and immune markers, and imaging findings have been the focus of studies aimed at the early prediction of local recurrence and treatment response (23,24).…”
Section: Editorialmentioning
confidence: 99%